Pendidikan Islam dan Implikasinya Terhadap Sosial Keagamaan di Desa Cipanas Kabupaten Lebak - Mutaqin, Mumu Zainal; Junaidah, Emy (STAI Asy-Syukriyyah, 2025)
The research aims to explore Islamic education in an effort to socialize Islamic teachings, because education has an interest in internalizing the values of faith, piety and morals. So that the community has a religious commitment in developing knowledge and skills for charity and work which in turn creates a religious culture. This study uses qualitative research with a conscious enographic approach to understand various events that occur in society. Data collection techniques in the form of observation, interviews and documentation with informants, namely the residents of the village of Cipanas totaling three people related to the value of Islamic education and its implications for socio-religious. The values contained in Islamic education can grow and save themselves and their citizens from moral and ethical damage. In addition, the urgency is to foster balanced happiness by providing guidance so that they have noble character and all their actions are always guided by Islamic teachings. Rather, it is to increase the spiritual values of society and family in social relations within a framework of practices that are filled with values and morals.